PEMETAAN PERAN DAN FUNGSI KOMPONEN DALAM EKOSISTEM PENDIDIKAN DI KOTA METRO PROVINSI LAMPUNG - Khaidarmansyah -; Elsavivia Rusdi (Jurnal Bisnis Darmajaya, 2018)
In line with the objective of the establishment of the Republic of Indonesia, namely to educate the nation's life, the Ministry of National Education in its Strategic Plan has launched a theme “The formation of Persons and Ecosystems of Education and Culture that are characterized by the spirit of mutual cooperation”. This government commitment shows that education development must be carried out from various aspects, both from the aspect of education providers, and from the education process itself. The Metro City of Lampung Province as a city of education also has the same commitment as the central government, where in the 2016- 2021 Medium Term Development Plan carries education as a central theme in regional development policies. The spirit of the educational ecosystem proclaimed by the central government is also a reference in the development of education, but this has not been fully understood by all components of education in the Metro City education ecosystem. This research uses a qualitative method with a grounded theory approach. Analysis activities are carried out in the form of coding. There are two analytical procedures that are the basis for the coding process, namely; (a) making continuous comparisons; and (b) submitting questions. The research population is all education stakeholders, including students and education staff, parents, community organizations engaged in education and the Metro City Government. The results of the research show that not all components in the education ecosystem in Metro city understand their respective roles and functions, both core components, feeding components, and supporting components. Closer collaboration needs to be established between parents, educators and education staff, and school committees.Keywords - Educational Component, Educational Ecosystem